Empirical relationship between nifH gene abundance and diazotroph cell concentration in the North Pacific Subtropical Gyre. Issue 6 (22nd November 2022) - Gradoville, Mary R.; Dugenne, Mathilde; Hynes, Annette M.; Zehr, Jonathan P.; White, Angelicque E.
Abstract : Cyanobacterial N2 ‐fixing microorganisms (diazotrophs) play a critical role in nitrogen and carbon cycling in the oceans; hence, accurate measurements of diazotroph abundance are imperative for understanding ocean biogeochemistry. Marine diazotroph abundances are often assessed using qPCR of the nif H gene, a sensitive, taxa‐specific, and time/cost‐efficient method. However, the validity of nif H abundance as a proxy for cell concentration has recently been questioned. Here, we compare nif H gene abundances to cell counts for four diazotroph taxa ( Trichodesmium, Crocosphaera, Richelia, and Calothrix ) on two cruises to the North Pacific Subtropical Gyre, one of the largest habitats for marine diazotrophs. nif H:cell relationships were strong and significant for Crocosphaera, Richelia, and Calothrix ( nif H:cell 1.51–2.58; R 2 = 0.89–0.96) but were not significant for Trichodesmium, despite previous studies reporting significant nif H:cell relationships for this organism. Limited available data suggest that empirical nif H:cell can vary among studies but that relationships are usually significantly linear and >1:1. Our study indicates that nif H gene abundance, while not a direct measure of cells, is a useful quantitative proxy for diazotroph abundance.